Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Barisan Dan Deret Aritmatika Ditinjau Dari Kemampuan Komunikasi Matematika Di Kelas Xi Smk N 1 Air Joman - Antika, Cici (Universitas Asahan, 2026)
This study aims to describe the mistakes of students in solving problems on the arithmetic sequence and series material in terms of mathematical communication skills. This type of research is descriptive qualitative. The subjects of this study were 27 class XI students of SMK Negeri 1 Air Joman for the 2019/2020 academic year. The test instrument used in this study was in the form of 3 test questions that referred to indicators of mathematical communication skills including (1) expressing mathematical ideas or problems through writing, (2) using terms, notations, and mathematical symbols in presenting problems. mathematics, (3) expressing mathematical ideas or problems visually in the form of graphs, diagrams or tables, (4) interpreting mathematical ideas or problems in their own language, and (5) drawing conclusions from mathematical statements. Based on the results of the study, it was concluded that students made mistakes in answering question number 1 as much as 48%, students 'errors in answering question number 2 were 26%, and students' errors in answering question number 3 were 38%.